COMPARISON OF CORONARY HEART DISEASE MORTALITY IN MEN AND WOMEN AGE 50 YEARS AND OLDER IN RUSSIA AND USA - S. A. Boytsov; O. V. Zayratiants; E. M. Andreev; I. V. Samorodskaya (Российский кардиологический журнал)
Aim. To compare mortality parameters in coronary heart disease (CHD) in Russia and USA, and to assess the reasons for differences; to underline the necessity for adequate completion of death certificates.Material and methods. Age-related and standardized mortality coefficients (SMC) for ages older than 50, in Russia and the US, were calculated, that are relevant to three- and four-digit codes of the “International Statistical Classification of Diseases and Related Health Problems, 10th”. As a standard for mortality coefficients, the European Standard Population (ЕСН-2013) was applied.Results. SMC from all types of CHD among men 50 years and older in RF was 2153,1, and in USA 712,6; among women, respectively, 1288,3 and 421,2. The part of deaths from “acute” CHD was 19,5% and 34,2% (males, RF and USA), 14,9% and 34,7% (females, RF and USA). Mortality from myocardial infarction (MI) (ICD-X code I21) in Russia is 1,6 times lower than in the USA, but by the chart “Other forms of acute ischemic heart disease”, I24) mortality in RG among women is 22 times higher, and in men — 35 times. The article discusses such discrepancies.Conclusion. Differences in mortality from CHD in the US and Russia are due to a range of reasons, many of them related to selection of primary cause of death and specifics of ICD-X code selection.